DEVELOPMENT ON NABEEZ TABLET ENRICHED WITH ANTIOKSIDAN CONTENT - Palal, Nor Hairul; M Salbi, Noorsabrina; Abdul Rahim, Rahimawati (Jurnal ’Ulwan, 2023)
The development of a sunnah drink known as Nabeez is a drink produced from soaked dates and raisins. This drink had high nutritional value content in addition to having an antioxidant content that can slow the growth of cancer. This drink began to gain a place among those who make sunnah food as a daily practice in addition to the fact that it is usually taken in the month of Ramadan as the main energy supply. Accordingly, the development of this Nabeez tablet product was aimed to optimize the antioxidant content of Nabeez and make it convenient for consumers. The study was conducted by obtaining the best formulation through three formulations (902, 835 and 276). The raw material antioxidant (raisins and dates) was firstly treated with Ultraviolet-C (UV-C) light for 180 seconds through a UV lamp at a radiation rate of 254nm with a distance of 22cm. The formulations produced were then evaluated by 30 trained panelists. The results showed that formulation 902 was chosen as the best formulation where through ANOVA-Test, P-values greater than 0.05 indicates significant difference between samples. Lastly, the Total Phenolic Content (TPC) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) was conducted for the finalized formulation Nabeez juice (23.8%), maltodextrin (23.8%), Vitamin C powder (23.75%), Sodium Carbonate (23.74%), grape flavor (3.54%), aspartame (1.11%) and caramel color (0.26%). The development of the best formulation also showed the TPC was 1.7454 mg GAE/mg and DPPH was 79.71%. This Nabeez drink will not only be of interest to drink enthusiasts sunnah and will be an attraction for those who like detox drinks.